2008
DOI: 10.1080/10438590701222987
|View full text |Cite
|
Sign up to set email alerts
|

Absorptive Capacity and Innovation in the Knowledge Intensive Business Service Sector

Abstract: Innovative activity is performed to a considerable extent in the service sector, namely within the so-called knowledge intensive business services (KIBS). Particularly emphasizing the role of absorptive capacity, we analyze possible determinants of incremental and radical firm innovation using firm micro data from the KIBS Foundation Survey. The results show that access to knowledge through networking and cooperation is of utmost importance for innovative activity in the KIBS sector. Access to knowledge from u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(53 citation statements)
references
References 49 publications
2
48
2
1
Order By: Relevance
“…By transmitting codified and tacit knowledge to their clients, KIBS influence the innovation process by producing, transferring and recombining innovations in cooperation with their client firms (den Hertog, 2000). Therefore, KIBS drive knowledge-changing processes and offer produced knowledge (Strambach, 2008), which is positively affected by customers with a high degree of formalized knowledge in the respective field (Koch and Strotmann, 2008). In comparison to the manufacturing sector, KIBS require networks to disseminate innovation due to the highly immaterial nature of KIBS and the requirement of human-intensive interactions (Koch and Strotmann, 2008;Koschatzky, 1999, p. 752).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…By transmitting codified and tacit knowledge to their clients, KIBS influence the innovation process by producing, transferring and recombining innovations in cooperation with their client firms (den Hertog, 2000). Therefore, KIBS drive knowledge-changing processes and offer produced knowledge (Strambach, 2008), which is positively affected by customers with a high degree of formalized knowledge in the respective field (Koch and Strotmann, 2008). In comparison to the manufacturing sector, KIBS require networks to disseminate innovation due to the highly immaterial nature of KIBS and the requirement of human-intensive interactions (Koch and Strotmann, 2008;Koschatzky, 1999, p. 752).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, KIBS drive knowledge-changing processes and offer produced knowledge (Strambach, 2008), which is positively affected by customers with a high degree of formalized knowledge in the respective field (Koch and Strotmann, 2008). In comparison to the manufacturing sector, KIBS require networks to disseminate innovation due to the highly immaterial nature of KIBS and the requirement of human-intensive interactions (Koch and Strotmann, 2008;Koschatzky, 1999, p. 752). Potential difficulties in using KIBS involve the complexity of cooperation, caused by the high degree of human interaction and learning process required (Martínez-Argüelles and Rubiera-Morollón, 2006;Wood, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, it is important for firms to build a network of collaborative connections with external actors, such as customers, suppliers, dealers, and even competitors, which allow firms to gain control in the search and selective permeability of knowledge into organizational boundaries (Chen et al, 2009). The recognition and absorption of new and related external knowledge, generates motivations which lead organizations to set continuous relationships with their external network partners, and establish technological cooperation agreements (Koch & Strotmann, 2008;Murovec & Prodan, 2009). Here, reliable, fast and qualified knowledge sharing among the relationship network allows firms to effectively organize and alleviate resources that are targeted to specific customer needs and wants, stimulating product innovation process (Chen et al, 2009).…”
Section: Absorptive Capacity and Firm Product Innovativenessmentioning
confidence: 99%
“…In a second study, Koch and Strotmann (2008) analyze the impact of founder characteristics on the innovation performance of German start-ups in the knowledge-intensive business sector. They distinguish two categories of innovation performance, incremental innovation, and radical innovation.…”
Section: Comparison With Existing Empirical Literaturementioning
confidence: 99%
“…at the earliest in 1989. In a second study, Koch and Strotmann (2008) analyze the impact of founder characteristics on the innovation performance of German start-ups in the knowledge-intensive business sector. In both studies, managerial characteristics and founder characteristics, respectively, showed rather low explanatory power.…”
Section: Introductionmentioning
confidence: 99%